2018
DOI: 10.5603/fm.a2017.0078
|View full text |Cite
|
Sign up to set email alerts
|

Examination of foramen tympanicum: an anatomical study using cone-beam computed tomography

Abstract: Considering that FT was present in 11.75% of patients, radiologists and clinicians should be aware of the possible presence of this defect. It is known that this developmental dehiscence may cause herniation of temporomandibular joint, formation of salivary otorrhea, and spread of tumour or infection to the infratemporal fossa from external auditory canal. This study showed that CBCT may be preferred for imaging these conditions. (Folia Morphol 2018; 77, 2: 335-339).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…Peris-Celda et al reported that the SSC dehiscence can be observed approximately 1.5 cm posterior to the middle point of the EAM in 86% of the cases [9]. In newborn, the tympanic membrane is infiltrated with air and the tympanic ring forms a bony plate, which may cause the development of a cleft, the auricular fissure, posteriorly and a cleft, the tympano-squamous fissure, anteriorly [19,20].…”
Section: Surgical Landmarks and Ossification Of The Tympanic Portionmentioning
confidence: 99%
See 4 more Smart Citations
“…Peris-Celda et al reported that the SSC dehiscence can be observed approximately 1.5 cm posterior to the middle point of the EAM in 86% of the cases [9]. In newborn, the tympanic membrane is infiltrated with air and the tympanic ring forms a bony plate, which may cause the development of a cleft, the auricular fissure, posteriorly and a cleft, the tympano-squamous fissure, anteriorly [19,20].…”
Section: Surgical Landmarks and Ossification Of The Tympanic Portionmentioning
confidence: 99%
“…Medially, it fuses with the petrous portion, whereas a free lateral part of it constructs the major part of the EAM and also serves an attachment for the cartilaginous part of the external auditory canal (EAC). Its inferior margin is free, and it has two parts on the lateral surface; posterosuperior part forms the EAM, and anteroinferior part limits the mandibular fossa posteriorly [5,19].…”
Section: The Tympanic Portionmentioning
confidence: 99%
See 3 more Smart Citations